Histone Acetylation and Methylation Underlie Oligodendroglial and Myelin Susceptibility in Schizophrenia - Li, Mei; Xiao, Lan; Chen, Xianjun (Frontiers in Cellular Neuroscience, 2022)
Schizophrenia is a complex neuropsychiatric disorder affected by both genetic and epigenetic factors. Except for neuronal dysfunction, oligodendroglial abnormalities also contribute to the disease pathogenesis, characterized by a robust dysregulation of oligodendrocyte and myelin related genes. Accumulating evidence shows that histone modifications play important roles in transcriptional regulation of the genes crucial for oligodendrocyte differentiation and myelination. Specifically, the histone acetylation and methylation were two well-recognized histone modification abnormalities in the schizophrenic brains. In this mini-review, we will describe the dynamic changes of histone acetylation and methylation in schizophrenia, which may coordinate and induce deleterious epigenetic memory in oligodendroglial cells, and further lead to oligodendrocyte and myelin deficits. Precise modulation of histone modification status in oligodendroglial cells needs to secure the balance of epigenetic marks, which may revise the therapeutic strategy for the white matter etiology of neuropsychiatric disorders.